Jugular thrombophlebitis in horses subjected to laparotomy for the treatment of gastrointestinal disease - Montanhim, Gabriel L. [UNESP]; Toni, Maria C. [UNESP]; Sousa, Samuel S. [UNESP]; Bonacin, Yuri S. [UNESP]; Bueno, Gabriela M. [UNESP]; Módolo, Tiago J.C. [UNESP]; Santana, Aureo E. [UNESP]; Dias, Deborah P.M. [UNESP] (FapUNIFESP (SciELO), 2018)
Coagulation abnormalities are usually associated with equine gastrointestinal disease due to the increased levels of inflammatory mediators, which promotes hemostasis and inhibit fibrinolysis, creating a hypercoagulable state. Horses underwent laparotomy to treat colic usually require a venous catheter for several days to administrate fluids and drugs during the postoperative period, and the jugular vein is the most frequent site for catheterization. Therefore, the persistent vascular trauma caused by an implanted catheter, associated with the prothrombotic environment induced by the gastrointestinal disorder, increases the risk for the development of jugular thrombophlebitis. The purpose of the present investigation was to evaluate physical and ultrassonographic features of the jugular vein cannulated with a polyurethane catheter during the postoperative period of horses underwent colic surgery. The catheter was inserted aseptically on admission and dwell time was seven days. Upon ultrasound examination, one horse developed thrombophlebitis 48 hours after surgery and the other horses showed thickened venous wall at puncture site and small clots associated to the catheter. Ultrasound monitoration showed that long-term catheterization in horses underwent colic surgery following the present protocol minimizes vascular trauma and could prevent jugular thrombophlebitis.
Tromboflebite jugular em equinos submetidos à laparotomia para o tratamento de afecção gastrointestinal
Keywords: Catheter; Colic; Gastrointestinal disease; Horses; Jugular; Laparotomy; Surgery; Thrombophlebitis; Thrombus; Ultrasound